Digest: Positive selection and recombination shape the genomic landscape in flycatchers. (19th July 2021) - Wang, Yiguan; Narayan, Vikram
Abstract: Whether background selection is sufficient to explain observed genomic differentiation is a long‐standing debate. Using four species of flycatcher, Chase et al. addressed this issue and found that the effect of background selection may not be as great as previously thought. Instead, both positive selection and recombination were shown to have a significant effect on genomic differentiation.